HDL Isolated by Immunoaffinity, Ultracentrifugation, or Precipitation is Compositionally and Functionally Distinct - Michael Holzer; Senka Ljubojevic-Holzer; Douglas Ricardo Souza Junior; Julia T. Stadler; Alankrita Rani; Hubert Scharnagl; Graziella Eliza Ronsein; Gunther Marsche (Journal of Lipid Research, 2022)
The HDL proteome has been widely recognized as an important mediator of HDL function. While a variety of HDL isolation methods exist, their impact on the HDL proteome and its associated function remain largely unknown. Here, we compared three of the most common methods for HDL isolation, namely immunoaffinity (IA), density gradient ultracentrifugation (UC), and dextran-sulfate precipitation (DS), in terms of their effects on the HDL proteome and associated functionalities. We used state-of-the-art mass spectrometry to identify 171 proteins across all three isolation methods. IA-HDL contained higher levels of paraoxonase 1, apoB, clusterin, vitronectin, and fibronectin, while UC-HDL had higher levels of apoA2, apoC3, and α-1-antytrypsin. DS-HDL was enriched with apoA4 and complement proteins, while the apoA2 content was very low. Importantly, size-exclusion chromatography analysis showed that IA-HDL isolates contained subspecies in the size range above 12 nm, which were entirely absent in UC-HDL and DS-HDL isolates. Analysis of these subspecies indicated that they primarily consisted of apoA1, IGκC, apoC1, and clusterin. Functional analysis revealed that paraoxonase 1 activity was almost completely lost in IA-HDL, despite high paraoxonase content. We observed that the elution conditions, using 3M thiocyanate, during IA resulted in an almost complete loss of paraoxonase 1 activity. Notably, the cholesterol efflux capacity of UC-HDL and DS-HDL was significantly higher compared to IA-HDL. Together, our data clearly demonstrate that the isolation procedure has a substantial impact on the composition, subclass distribution, and functionality of HDL. In summary, our data show that the isolation procedure has a significant impact on the composition, subclass distribution and functionality of HDL. Our data can be helpful in the comparison, replication and analysis of proteomic datasets of HDL.